2001
DOI: 10.1002/ijc.1355
|View full text |Cite
|
Sign up to set email alerts
|

Hybrids of pluripotent and nullipotent human embryonal carcinoma cells: Partial retention of a pluripotent phenotype

Abstract: To investigate whether the failure of human EC cells that do not differentiate is due to the loss of key differentiationpermissive functions or the acquisition of specific inhibitory functions, we tested the ability to differentiate of 2 hybrids produced between a relatively nullipotent human EC cell line, 2102Ep, and a pluripotent human EC cell line NTERA2. Both hybrids, which exhibited an EC phenotype, were able to differentiate readily in response to retinoic acid. Furthermore, 1 hybrid produced a well-diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…These observations on an established human EC line are in line with previous reports of osteogenic characteristics in mouse EC-derived lines [Poliard et al, 1993;Shukunami et al, 1997]. The differentiation ability of existing human EC lines is heterogeneous [Pera et al, 1989;Duran et al, 2001]. NTera2 cells originate from a human testicular EC and have been well characterized, including their propensity to form neuroectodermal lineages in response to retinoic acid [Andrews et al, 1984;Andrews, 2002].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These observations on an established human EC line are in line with previous reports of osteogenic characteristics in mouse EC-derived lines [Poliard et al, 1993;Shukunami et al, 1997]. The differentiation ability of existing human EC lines is heterogeneous [Pera et al, 1989;Duran et al, 2001]. NTera2 cells originate from a human testicular EC and have been well characterized, including their propensity to form neuroectodermal lineages in response to retinoic acid [Andrews et al, 1984;Andrews, 2002].…”
Section: Discussionsupporting
confidence: 78%
“…Injections into mouse models indicate that human EC lines can form tumours containing a broad range of tissues, occasionally including cartilage [Pera et al, 1989;Andrews, 2002]. However, this differentiation has not been widely reported for NTera2 [Duran et al, 2001], and so far, reports describing their in vitro potential suggest a limited range of mesodermal cell types in NTera2 cultures [Chadalavada et al, 2005;Pal and Ravindran, 2006;Simoes and Ramos, 2007]. Our study provides new evidence that NTera2 cultures can deposit minerals in vitro after OM treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Fielding et al (57) reported that cholesterol and other sterols have the ability to alter caveolin-1 mRNA levels. Therefore, to ensure that the contents of our high serum media did not cause caveolin-1 expression to be altered independent of the differentiation process, we employed a control cell line, 2102Ep, which is a human embryonic carcinoma cell line that is unable to differentiate (35,58) and thereby also does not undergo EMT. After receiving identical stimulation as the NT2/D1 cells, indeed, no morphological changes occurred in these cells.…”
Section: Stimulated Nt2/d1 and Nmumg Cells Both Undergo Emt-mentioning
confidence: 99%
“…Further, we wanted to determine the impact of caveolin-1 on aspects of cancer cell adhesion, because of the implicated role of caveolin in cell motility (18,19,34). The pluripotent human embryonic carcinoma cell line NT2/D1 has the potential to differentiate into a variety of cell types upon appropriate stimulation (35)(36)(37) and can accordingly undergo EMT. It is well documented that the mouse mammary epithelial cells NMuMG undergo EMT upon treatment with TGF-␤1 (38).…”
mentioning
confidence: 99%
“…In another study, we had investigated the behaviour of hybrid cells produced by fusing a pluripotent human EC cells from the NTERA2 line with nullipotent human EC cells from the 2102Ep line (Duran et al, 2001). NTERA2, but not 2102Ep, EC cells differentiate in response to retinoic acid, producing neurons as well as a range of other cell types (Andrews, 1984;Andrews et al, 1982;Matthaei et al, 1983).…”
Section: Introductionmentioning
confidence: 99%